BIOCONTROL POTENTIALITIES OF NATIVE PSEUDOMONAS ISOLATES AGAINST PLANT PATHOGENIC FUNGI RHIZOCTONIA SPP., FUSARIUM SPP. AND COLLETOTRICUM SPP. IN TOMATO RHIZOSPHERE UNDER GREEN HOUSE CONDITION. - SWATI ROSE TOPPO; PREETI TIWARI (The Bioscan, 2015)
A total of four Pseudomonas isolates were obtained from rhizospheric soil of Korea district of Chhattisgarh, India. Two were identified as Pseudomonas syringae, another two were as Pseudomonas alcaligenes from IARI Delhi. Soil Pseudomonas spp. were examined for their antagonistic effect on a fungal pathogen Fusarium spp., Rhizoctonia spp. and Colletotrichum spp. in in-vitro plate assay and in-vivo green house condition. The result from in-vitro analysis showed that PKJ25 was the most active isolate and significantly suppressed the vegetative growth of all the test fungi by restricting the hyphal growth of Rhizoctonia spp., Fusarium spp. and Colletotricum spp. to 0.73, 1.54 and 2.01cm with 91.20%, 78.90% and 77.67% inhibition. In vivo, PKJ25 had the least disease incidence in tomato and highest percent disease control. The survival % of tomato plantlets was significantly higher with isolate PKJ25 in comparison to other isolates and was recorded 93% in case of damping off due to Rhizoctonia spp. , 86% in case of wilt due to Fusarium spp., 86% in case of fruit anthracnose due to Colletotrichum spp. This result shows that Pseudomonas isolate PKJ25 (Pseudomonas alcaligenes) was very effective biocontrol agents and should be exploited for further biocontrol applications.